2022
DOI: 10.2147/idr.s384442
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Outcomes of Spinal Tuberculosis in Central China

Abstract: Purpose The appropriate management of spinal tuberculosis (TB) is challenging for clinicians and the key to treat spinal TB. Surgery and long course anti-TB chemotherapy may not be necessary to all situations. This study aimed to characterize the clinical features and factors affecting treatment outcomes. Patients and Methods A retrospective study of patients with spinal TB over a 5-year period at a teaching hospital in central China was conducted. Features of patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…A multicenter study demonstrated that the monocyte-to-lymphocyte ratio (MLR) and neutrophil-to-lymphocyte ratio (NLR) were notably greater in patients with active tuberculosis than in those with latent tuberculosis 34 . Additionally, well-known indicators,such as ESR and CRP concentration, are commonly used to evaluate the degree of inflammation in patients with tuberculosis 35 and are associated with the prognosis of STB 36 , 37 . Nutritional status is also a vital factor affecting the progression and prognosis of spinal tuberculosis patients, and research has shown that the serum ALB concentration is an important laboratory marker for predicting SCI and prognosis in STB patients 38 .…”
Section: Discussionmentioning
confidence: 99%
“…A multicenter study demonstrated that the monocyte-to-lymphocyte ratio (MLR) and neutrophil-to-lymphocyte ratio (NLR) were notably greater in patients with active tuberculosis than in those with latent tuberculosis 34 . Additionally, well-known indicators,such as ESR and CRP concentration, are commonly used to evaluate the degree of inflammation in patients with tuberculosis 35 and are associated with the prognosis of STB 36 , 37 . Nutritional status is also a vital factor affecting the progression and prognosis of spinal tuberculosis patients, and research has shown that the serum ALB concentration is an important laboratory marker for predicting SCI and prognosis in STB patients 38 .…”
Section: Discussionmentioning
confidence: 99%